2013
DOI: 10.1093/hmg/ddt425
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive transplantation of iPSC-derived ALDHhiSSCloVLA4+ neural stem cells effectively improves the phenotype of an amyotrophic lateral sclerosis model

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disease characterized by the degeneration of motor neurons. Currently, there is no effective therapy for ALS. Stem cell transplantation is a potential therapeutic strategy for ALS, and the reprogramming of adult somatic cells into induced pluripotent stem cells (iPSCs) represents a novel cell source. In this study, we isolated a specific neural stem cell (NSC) population from human iPSCs based on high aldehyde dehydrogenase activity, low side scatter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 29 publications
(78 reference statements)
1
70
0
2
Order By: Relevance
“…This neuroprotection correlated with decreased inflammation, as shown by a decrease in the proliferation of microglial cells and reduced expression of inflammatory-related genes, COX-2 and NOX-2 [75] . Recent publications confirmed that transplantation of stem cells indeed reduces neuroinflammation and suggests that alleviating astrocytosis or microgliosis is an important parameter leading to both histological and functional improvement in ALS animal models [144,145] . Another approach was tested by Mitrecić et al [135] .…”
Section: Lessons From Transplantation Paradigms In Als Modelsmentioning
confidence: 93%
“…This neuroprotection correlated with decreased inflammation, as shown by a decrease in the proliferation of microglial cells and reduced expression of inflammatory-related genes, COX-2 and NOX-2 [75] . Recent publications confirmed that transplantation of stem cells indeed reduces neuroinflammation and suggests that alleviating astrocytosis or microgliosis is an important parameter leading to both histological and functional improvement in ALS animal models [144,145] . Another approach was tested by Mitrecić et al [135] .…”
Section: Lessons From Transplantation Paradigms In Als Modelsmentioning
confidence: 93%
“…In a series of longterm studies, Chen et al showed iPSC-derived neural progenitors mostly differentiated into astrocytes, replaced the endogenous astrocytes, formed networks through their processes, and encircled endogenous neurons [68]. Preclinical studies, currently being conducted at Johns Hopkins University, use human iPSC-derived glial-restricted precursors (iPSC-GRPs) [88] and may offer perspectives for the use of iPSC-based therapy in ALS [87].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Alternatively, intrathecal injection of stem cells could allow for more targeted administration of stem cells into the CNS although penetration of the cells from the cerebrospinal fluid into the parenchyma may still be a significant hurdle to overcome. In a recent study, Nizzardo et al (2014) compared the delivery of human induced pluripotent stem cell-derived neural stem cells by either intrathecal or intravenous delivery in the SOD1 G93A mouse model of ALS. To enhance the homing potential of stem cells to enter the parenchyma after intravenous delivery, the authors used fluorescence activated cell sorting (FACS) to isolate a population of human induced pluripotent stem cell-derived neural stem cells expressing the VLA4 integrin allowing for enhanced binding to the blood-brain-barrier via adhesion molecules .…”
Section: Challenges In Translation Of Stem Cell Therapiesmentioning
confidence: 99%
“…Human induced pluripotent stem cells are self-renewing, largely expandable, and can differentiate to endoderm, ectoderm, or mesoderm germ lineages. Indeed, recent reports show that human induced pluripotent stem cells differentiated to neural progenitor lineages can be engrafted to the spinal cord of the SOD1 mouse model of ALS with modest phenotypic improvement (Kondo et al, 2014;Nizzardo et al, 2014). In addition to the avoidance of ethical issues, human induced pluripotent stem cells offer another potential advantage for cell therapy since they can be reprogrammed directly from cells isolated from a patient biopsy.…”
mentioning
confidence: 99%